Anesthetic management for cesarean section in parturient with an uncorrected single ventricle - Yu Du, PhD; Yingzi Yang-Liu, MD; Bin Chen, MD; Ji Wang, PhD (Medicine, 2022)
Abstract. Rationale:. Patients with a single ventricle, who have not undergone surgery, reportedly have a lower survival rate. Furthermore, multiple pregnancies are rare among these females. We reported a case of anesthesia management of cesarean section in an uncorrected single-ventricular multi-pregnancy woman and review the anesthesia management of the published similar cases. Patient concerns:. An uncorrected single ventricular pregnant woman with a cardiac function of New York Heart Association class II, who had experienced one spontaneous abortion and three vaginal deliveries, was scheduled for cesarean section at 37+6 weeks of gestation. Diagnoses. : Echocardiography revealed a complex congenital heart disease in the mother: a single ventricle (the left ventricle is dominant), atrioventricular valve ectopic, double-inlet left ventricle, abnormal location of the great arteries, probably pulmonary stenosis, atrial septal defect, and left-to-right shunt. The fetus was in breech presentation with umbilical cord around the neck. Interventions:. Cesarean section was successfully performed under the combined spinal epidural anesthesia with careful monitoring. Outcomes. : Both mother and newborn recovered good and were discharged from the hospital 5 days after surgery without any adverse reactions. Lessons:. Single ventricular pregnant woman with a cardiac function of New York Heart Association class I–II could tolerate pregnancy and delivery well. Both general and regional anesthesia are applicable to cesarean section in these patients. The principle of anesthesia management is to maintain the appropriate balance between systemic vascular resistance and pulmonary vascular resistance, as well as to maintain preload and cardiac output.